Conflict resolution - "Kataria, Pooja" (New Delhi, 2007)
Book Summary of Conflict Resolution : Conflict Forms, Causes And Methods Of Resolution This book gives a theoretical foundation of the forms and causes of conflicts, methods of conflicts, various regional and international conflicts and Gandhian approach to conflict resolution.
Keywords: "Conflict-Forms, causes"